Molecular survey of Babesia parasites in Kenya: first detailed report on occurrence of Babesia bovis in cattle - Githaka, Naftaly W.; Bishop, Richard P.; Šlapeta, J.; Emery, D.; Nguu, E.K.; Kanduma, E.G. (Springer, 2022)
Background Among protozoan parasites in the genus Babesia, Babesia bigemina is endemic and widespread in the East African region while the status of the more pathogenic Babesia bovis remains unclear despite the presence of the tick vector, Rhipicephalus microplus, which transmits both species. Recent studies have confirmed the occurrence of R. microplus in coastal Kenya, and although B. bovis DNA has previously been detected in cattle blood in Kenya, no surveillance has been done to establish its prevalence. This study therefore investigated the occurrence of B. bovis in cattle in Kwale County, Kenya, where R. microplus is present in large numbers.